Phylogenetic implications and secondary structure analyses of Vigna mungo (L.) Hepper genotypes based on nrDNA ITS2 sequences. (February 2019) - Sheth, Bhavisha P.; Punia, Sumer; Dheer, Meenakshi; Rakhashiya, Purvi M.; Patel, Pooja P.; Thaker, Vrinda S.
Abstract: The internal transcribed spacers are highly preferred nuclear markers for the phylogenetic assessment of most eukaryotes, including plants. More recently, ITS2 has shown to possess equivalent phylogenetic significance as the entire ITS region. Vigna mungo L. Hepper is comparatively less explored from the molecular aspects as compared to the other species of the Vigna genus. The study presents the intra-individual characterization of 24 distinct genotypes Vigna mungo L. Hepper, using morphological as well as nrDNA ITS2 sequences and secondary structural data. The morphological characterization has been carried out using nine important agro-morphological traits. The molecular phylogeny of the sequence data, using the maximum parsimony and neighbor joining methods, shows the significant distinction based on the haplotypic variations amongst blackgram genotypes. The ITS2 secondary structures predicted using the homology modeling approach were compatible with the eukaryote-universal ITS2 secondary structure. The sequence-structure phylogeny reconstructed using the profile neighbour joining approach, also showed the presence of haplotypic variations in form of clusters on the phylogenetic tree. Further, the high GC content in the sequence data and highly negative ΔG values of the folded secondary structures ruled out the possibilities of the presence of any pseudogenes in the data set. Our analysis recommends the use of ITS2 sequence and secondary structure data at the intraspecific levels of plant taxonomical classification. Moreover, this study for the very first time reports the combined use morphological, and molecular data (using ITS2 sequence and secondary structural information) for the characterization of plants at the varietal level of taxonomical classification.